Heyzine Flipbooks-Assisted E-Module Training in Science Learning for Junior High School Students: Pelatihan Penggunaan E-Modul Berbantuan Heyzine Flipbooks dalam Pembelajaran IPA Siswa di SMP - Wahyuni Arafani; Nurul Hidayah; Devi Karisna Putri; Muhammad Al Awali Salahuddin (Jurnal Pengabdian Masyarakat Tropis Indonesia, 2025)
Technological advancements require teachers to be more creative in developing interactive and engaging teaching materials. However, in many schools, teaching materials are still dominated by printed books without any digital media variations. This community service activity aims to improve teachers' skills in developing and implementing Science E-Modules using Heyzine Flipbooks and to assess students' responses to their use. The methods used included discussion, mentoring, and practice, which were carried out in three stages: preparation, implementation, and evaluation. The results of the activity showed that teachers felt helped in converting printed modules into more interactive E-Modules, and students gave very positive responses with an average score of 85%, categorized as very practical and engaging. In conclusion, the use of flipbook-based Science E-Modules is effective in improving the quality of science learning at the junior high school level and can be an alternative solution in the development of digital teaching materials.